A Study of the Ampang Landfill Leachate Characteristics and its Effects on River Water Quality Parameters - Kamal Batcha, Fatimah; P, Agamuthu,; Ibrahim, Shaliza (Malaysian Journal of Science, 2003)
Physical and inorganic parameters have been measured for leachate from the Ampang Municipal Landfill before and after the landfill was closed. Although there were significant reduction in the parameter concentrations after the landfill closure, the COD value was still 20 times higher than the requirement of EQA 1974 Standard A. BOD, TSS, Fe, Mg, Cd and Pb were also higher than the Standards requirements after closure. The effects of leachate seeping into the Michu River, have been investigated through analyses of water samples taken along the Michu and Langat Rivers up to the Puncak Niaga Langat River water intake point. Reduction in the parameter values occurred with increase in time from the closure and distance from the leachate source. Occasional increase in the parameter values at certain sampling stations could be attributed to discharge from various anthropogenic activities upstream. However, geogenic aspects such as the impact of river hydraulics on microscopic conditions could also be important in determining the quality of river water. These factors, however, were beyond the scope of this study.Physical and inorganic parameters have been measured for leachate from the Ampang Municipal Landfill before and after the landfill was closed. Although there were significant reduction in the parameter concentrations after the landfill closure, the COD value was still 20 times higher than the requirement of EQA 1974 Standard A. BOD, TSS, Fe, Mg, Cd and Pb were also higher than the Standards requirements after closure. The effects of leachate seeping into the Michu River, have been investigated through analyses of water samples taken along the Michu and Langat Rivers up to the Puncak Niaga Langat River water intake point. Reduction in the parameter values occurred with increase in time from the closure and distance from the leachate source. Occasional increase in the parameter values at certain sampling stations could be attributed to discharge from various anthropogenic activities upstream. However, geogenic aspects such as the impact of river hydraulics on microscopic conditions could also be important in determining the quality of river water. These factors, however, were beyond the scope of this study.